Immigration and Education: Early Insights from the Buslift to New York City - Selen Ozdogan; Kevin Y. Shih (Institute of Labor Economics (IZA), 2025)
Since 2022, New York City has received more than 200,000 asylum-seekers from the southern border, many of whom were young children. Families were placed in homeless shelters, with children subsequently enrolled in nearby public elementary schools. Exploiting variation in homeless shelter capacity across school zones, we show that exposed schools saw increases in migrant students, proxied by English Language Learners, Hispanic students, and students in temporary housing. Despite these shifts, domestic students did not experience adverse impacts on enrollment, test scores, attendance, or chronic absenteeism. Progressive funding helped buffer schools against resource crowding, expanding English language instruction to accommodate newcomers.
Keywords: I22; I29; J60; 330; immigration; education; asylum-seekers